Los tres García - Rodríguez Ruelas, Ismael, 1917-; Infante, Pedro, 1917-1957; García, Sara, 1895-1980; Salazar, Abel; Mendoza, Victor Manuel (Warner Bros., 2007)
Tres hermanos salvajes se enamoran de la misma chica con resultados desastrosos.